IL-21 Receptor Blockade Shifts the Follicular T Cell Balance and Reduces De Novo Donor-Specific Antibody Generation - Nian, Yeqi; Xiong, Zhilei; Zhan, Panpan; Wang, Zhen; Xu, Yang; Wei, Jianghao; Zhao, Jie; Fu, Yingxin (Frontiers in Immunology, 2021)
Donor-specific antibodies (DSAs) play a key role in chronic kidney allograft injury. Follicular T helper (Tfh) cells trigger the humoral alloimmune response and promote DSA generation, while T-follicular regulatory (Tfr) cells inhibit antibody production by suppressing Tfh and B cells. Interleukin (IL)-21 exerts a distinct effect on Tfh and Tfr. Here, we studied whether blocking IL-21R with anti-IL-21R monoclonal antibody (αIL-21R) changes the Tfh/Tfr balance and inhibits DSA generation. First, we investigated the impact of αIL-21R on CD4+ T cell proliferation and apoptosis. The results showed that αIL-21R did not have cytotoxic effects on CD4+ T cells. Next, we examined Tfh and regulatory T cells (Tregs) in an in vitro conditioned culture model. Naïve CD4+ T cells were isolated from 3-month-old C57BL/6 mice and cultured in Tfh differentiation inducing conditions in presence of αIL-21R or isotype IgG and differentiation was evaluated by CXCR5 expression, a key Tfh marker. αIL-21R significantly inhibited Tfh differentiation. In contrast, under Treg differentiation conditions, FOXP3 expression was inhibited by IL-21. Notably, αIL-21R rescued IL-21-inhibited Treg differentiation. For in vivo investigation, a fully mismatched skin transplantation model was utilized to trigger the humoral alloimmune response. Consistently, flow cytometry revealed a reduced Tfh/Tfr ratio in recipients treated with αIL-21R. Germinal center response was evaluated by flow cytometry and lectin histochemistry. We observed that αIL-21R significantly inhibited germinal center reaction. Most importantly, DSA levels after transplantation were significantly inhibited by αIL-21R at different time points. In summary, our results demonstrate that αIL-21R shifts the Tfh/Tfr balance toward DSA inhibition. Therefore, αIL-21R may be a useful therapeutic agent to prevent chronic antibody mediated rejection after organ transplantation.